2017
DOI: 10.1103/physrevb.96.104306
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium ab initio molecular dynamics determination of Ti monovacancy migration rates in B1 TiN

Abstract: We use the color diffusion (CD) algorithm in nonequilibrium (accelerated) ab initio molecular dynamics simulations to determine Ti monovacancy jump frequencies in NaCl-structure titanium nitride (TiN), at temperatures ranging from 2200 to 3000 K. Our results show that the CD method extended beyond the linear-fitting rate-versus-force regime [Sangiovanni et al., Phys. Rev. B 93, 094305 (2016)] can efficiently determine metal vacancy migration rates in TiN, despite the low mobilities of lattice defects in this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 101 publications
(128 reference statements)
2
16
0
Order By: Relevance
“…We found that the migration energies for Ti V and N V in B1-TiN along <110> directions are 4.13 and 4.24 eV, respectively, with saddle-point transition states located halfway between initial and final atomic positions (Figure 7a). The MEAM predictions are in good agreement with DFT-NEB results, which yield energy barriers of ≈3.8 eV for N V [114] and 4.26 eV for Ti V [97]. Experimental values for vacancy migration energies in B1-TiN are scarce in the literature.…”
Section: Potential Validation Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…We found that the migration energies for Ti V and N V in B1-TiN along <110> directions are 4.13 and 4.24 eV, respectively, with saddle-point transition states located halfway between initial and final atomic positions (Figure 7a). The MEAM predictions are in good agreement with DFT-NEB results, which yield energy barriers of ≈3.8 eV for N V [114] and 4.26 eV for Ti V [97]. Experimental values for vacancy migration energies in B1-TiN are scarce in the literature.…”
Section: Potential Validation Resultssupporting
confidence: 70%
“…E f V values for N and Ti vacancies (N V and Ti V , respectively), obtained using a N atom in a N 2 molecule and of a Ti atom in hcp-Ti lattice as reference chemical potentials, are E f NV = 3.53 eV and E f TiV = 4.76 eV. The corresponding DFT-based values, found in the literature, lie in the ranges 2.41–2.53 eV (N V ) [95,96] and 2.86–3.11 eV (Ti V ) [96,97]. The discrepancy between MEAM and DFT results becomes less than 10% when using the chemical potential of isolated N and Ti for computing E f V .…”
Section: Potential Parametrization Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics simulations inherently resolve the problems mentioned above by integrating Newton's equations of motion for each atom at any temperature of interest. CMD/AIMD reaction rates for adspecies intra-and interlayer migration [22,59,60,68,111] or desorption [63,112], as well as point defects in bulk [110,113], can be employed in kinetic Monte Carlo simulations [114] to efficiently probe the effects of precursors fluxes and ion-to-metal ratios on film growth modes.…”
Section: Finite-temperature Aimd Resultsmentioning
confidence: 99%
“…Lattice anharmonicity is also known to cause deviations from an Arrhenius temperature-dependent behavior for thermodynamic and kinetic properties in bulk systems. For example, it is known that vacancy formation [106,107] and migration (or diffusion, i.e., defect formation + defect migration) energies [108][109][110] may vary considerably from 0 K up to the melting temperature. Molecular dynamics simulations inherently resolve the problems mentioned above by integrating Newton's equations of motion for each atom at any temperature of interest.…”
Section: Finite-temperature Aimd Resultsmentioning
confidence: 99%